Pengaruh Daya Tarik Dan Promosi Terhadap Keputusan Wisatawan Berkunjung Ke Objek Wisata Pongtorra’ Toraja Utara - Pundissing, Rati (UKI Toraja Press, 2021)
The purpose of this research is to analyze how the influence of the attractiveness and promotion on the decision of tourists to visit the tourist attraction Pongtorra' North Toraja Regency. The research method used is a quantitative method where the data derived from the questionnaires answers that have been quantified by weighting the respondent’s answers are analyzed statistically. The number of population in this study was 18,250 people from that population, a total sample size of 100 respondents. The results showed that attractiveness (X1) had a positive and significant effect on the Tourist Decision to Visit (Y) to the tourist attraction Pongtorra' North Toraja Regency. While Promotion (X2) has a positive and significant effect on the Tourist Decision to Visit (Y) to the tourist attraction Pongtorra 'in North Toraja Regency. Simultaneously Attractiveness (X1) and Promotion (X2) have a positive and significant effect on Tourist Decision to Visit (Y) to the tourist attraction Pongtorra' North Toraja Regency. The results of this study can be concluded that simultaneously the higher the attractiveness and promotion carried out by the manager, the higher the decision of tourists to visit, and vice versa.